Exploring healthcare personnel’s knowledge, barriers, and innovative approaches in personalised oncology medicine: a scoping review - Shibu Shrestha; Gemma Watts; Susi Geiger (Critical Public Health, 2025)
Personalised medicine is widely utilised in oncology, and healthcare personnel are its main gatekeepers and implementers. This scoping review provides insights into the knowledge and attitudes of healthcare personnel toward personalised medicine for cancer, barriers and challenges faced, and innovative practices employed for the provision of personalised medicine. Extensive database searches identified 19,972 studies, of which 50 studies were included in the final review. The data was charted by two reviewers and analysed thematically. The knowledge of healthcare personnel of personalised medicine was mixed, with some studies reporting overall good knowledge (n = 2) while some reported poor knowledge among healthcare personnel (n = 4). There was high interest (63–95%) in furthering education and training in personalised medicine (n = 6). The commonly reported barriers and challenges were: limited reimbursement and insurance coverage mechanism (n = 11); insufficient education and training (n = 10); and lack of trained personnel to provide the service (n = 7). The innovations identified emphasised enhancing the skills and capacity of the existing workforce as well as using technologies to assist in timely decision-making. Overall, gaps were identified at the human resource, institutional, and systemic levels, which will need to be addressed to improve the provision of personalised medicine and healthcare personnel’s confidence levels.